2015
DOI: 10.1002/jmr.2449
|View full text |Cite
|
Sign up to set email alerts
|

Screening of l‐histidine‐based ligands to modify monolithic supports and selectively purify the supercoiled plasmid DNA isoform

Abstract: The growing demand of pharmaceutical-grade plasmid DNA (pDNA) suitable for biotherapeutic applications fostered the development of new purification strategies. The surface plasmon resonance technique was employed for a fast binding screening of l-histidine and its derivatives, 1-benzyl-L-histidine and 1-methyl-L-histidine, as potential ligands for the biorecognition of three plasmids with different sizes (6.05, 8.70, and 14 kbp). The binding analysis was performed with different isoforms of each plasmid (super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Due to ability of L‐histidine and 1‐benzyl‐L‐histidine‐modified monoliths to recognize and separate pDNA isoforms from a pre‐purified sample , a thorough study of RNA removal from pDNA in a lysate sample was conducted, bringing new insights about the interactions promoted between histidine‐based ligands and nucleic acids. Initially, the elution strategies previously implemented for L‐histidine‐modified and 1‐benzyl‐L‐histidine‐modified monoliths were tested with the lysate sample and repeated at least three times by using stepwise gradients based on decreasing (NH 4 ) 2 SO 4 concentration from 2.94 to 0 M and from 2 to 0.8 and to 0 M of (NH 4 ) 2 SO 4 in 10 mM Tris‐HCl‐EDTA, pH 8.0, respectively. However, the co‐elution of sc pDNA and RNA was observed under these experimental conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to ability of L‐histidine and 1‐benzyl‐L‐histidine‐modified monoliths to recognize and separate pDNA isoforms from a pre‐purified sample , a thorough study of RNA removal from pDNA in a lysate sample was conducted, bringing new insights about the interactions promoted between histidine‐based ligands and nucleic acids. Initially, the elution strategies previously implemented for L‐histidine‐modified and 1‐benzyl‐L‐histidine‐modified monoliths were tested with the lysate sample and repeated at least three times by using stepwise gradients based on decreasing (NH 4 ) 2 SO 4 concentration from 2.94 to 0 M and from 2 to 0.8 and to 0 M of (NH 4 ) 2 SO 4 in 10 mM Tris‐HCl‐EDTA, pH 8.0, respectively. However, the co‐elution of sc pDNA and RNA was observed under these experimental conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Decarboxylated histidine (histamine ligand) has been successfully applied for pDNA isoforms separation using ion‐exchanging mechanism (ascending NaCl gradient) as well as HIC mechanism (descending ammonium sulfate gradient), proving its multimodality ). Moreover, a screening of the binding affinity of histidine‐based ligands (L‐histidine, 1‐benzyl‐L‐histidine and 1‐methyl‐L‐histidine) was recently performed by surface plasmon resonance biosensor for the biorecognition of three plasmids with different sizes, being achieved high affinity ( K D > 10 −8 M) of all ligands, especially with supercoiled pDNA isoform . The 1 H NMR spectra suggested that the imidazole ring of L‐histidine‐based ligands has an important role in interactions established with pDNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, our research group has been focused on the production and purification of the recombinant pDNA vaccine encoding E6 and E7 HPV16 oncoproteins . Thereby, the main purpose of this work was to conduct a differential in vitro comparison study to assess the expression of E6 and E7 proteins, resorting to the transfection of mammalian cells with pDNA samples obtained by different methods.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, our research group has been focused on the production and purification of the recombinant pDNA vaccine encoding E6 and E7 HPV16 oncoproteins. [8][9][10] Thereby, the main purpose of this work was to conduct a differential in vitro comparison study to assess the expression of E6 and E7 proteins, resorting to the transfection of mammalian cells with pDNA samples obtained by different methods. For this, it was our interest to compare a pDNA with 100% sc isoform homogeneity obtained with arginine monolith with a native pDNA sample, containing oc and sc isoform, retrieved by a commercial anion-exchange purification kit.…”
mentioning
confidence: 99%